Small-size stable water-soluble perovskite quantum dot composite material and preparation method and application thereof
By using potassium salt-doped 40nm molecular sieve on perovskite quantum dots for packaging, combined with the collapse packaging technology of high-temperature solid phase method, the problems of perovskite quantum dot stability and particle size in biological imaging applications are solved, and efficient fluorescence stability and biological imaging effects are achieved.
Patent Information
- Application Number
- CN202411662252.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The poor stability of the existing inorganic halide perovskite CsPbX3 in the environment limits its application development, especially in cell biological imaging, where molecular sieves with small particle size and uniform particle size are difficult to achieve effective encapsulation, resulting in low quantum yield of quantum dot fluorescence.
Perovskite quantum dots are encapsulated through a potassium salt-doped 40nm molecular sieve, and the encapsulated quantum dots are collapsed by high-temperature solid phase method. The inner wall salt of the molecular sieve passivates the quantum dots, reducing the defect density, and improving stability by using potassium salt as a sealing agent.
The water-resistant oxygen stability and fluorescence stability of perovskite quantum dots are achieved, ensuring efficient application of biological imaging, and simplifying the preparation process, avoiding the use of contaminated solvents, and having environmental protection advantages.
Smart Images

Figure CN119505898A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of luminescent materials, and in particular relates to a small-sized stable water-soluble perovskite quantum dot composite material and a preparation method and application thereof. Background Art
[0002] Novel inorganic metal halide perovskites (CsPbX3, X=Cl, Br, or I) have become promising candidates for numerous applications, such as light-emitting diodes, solar cells, lasers, photodetectors, photocatalysis, transistors, etc. This is related to the synergistic effect of their excellent properties, including high photoluminescence quantum yield, narrow and tunable emission, long charge carrier lifetime, wide absorption spectrum, and high extinction absorption coefficient. In recent years, the development of fluorescence microscopy has become more and more mature thanks to the development of fluorescent probes. The high photoluminescence quantum yield and large absorption cross-sectional area of the inorganic halide perovskite CsPbX3 show great application potential and commercial value in the nanotechnology of fluorescence microscopy as a fluorescent probe. However, the poor stability of the inorganic halide perovskite CsPbX3 in the environment severely limits its application development.
[0003] At present, the methods for improving pure inorganic PQDs are usually ligand passivation, oxide encapsulation and metal ion doping. The oxide encapsulation strategy has recently become an effective strategy to overcome stability problems and maintain the excellent performance of its nanomaterials. The prior art document 10.1038 / s41467-019-13881-0, Ceramic-like stable CsPbBr3nanocrystals encapsulated in silica derived from molecular sieve templates points out that by high-temperature calcination of oxide mesoporous silica (MCM-41 molecular sieve) and PQDs precursor, molecular sieve encapsulated PQDs can be prepared, which isolates water and oxygen from contact with PQDs to a certain extent, and improves the water and oxygen stability of PQDs. However, the molecular sieve used in this method has a large particle size and uneven particle size, which has great difficulties in application in cell biological imaging. Therefore, in order to give full play to the advantages of cell imaging, it is necessary to select molecular sieves with small and uniform particle size MSN to encapsulate perovskite quantum dots. However, small particle size will result in incomplete encapsulation of quantum dots, resulting in low fluorescence quantum yield of quantum dots and other problems. Therefore, how to effectively improve the stability of PQDs while avoiding the destruction of photoluminescence efficiency due to incomplete encapsulation of PQDs during the oxide MSN encapsulation process is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a small-sized stable water-soluble perovskite quantum dot composite material and its preparation method and application in order to overcome the defects of the above-mentioned prior art. The perovskite quantum dots are encapsulated by a 40nm molecular sieve doped with potassium salt, and the encapsulated quantum dots are collapsed by a high-temperature solid phase method to protect the quantum dots from corrosion by water and oxygen. The salt on the inner wall skeleton of the molecular sieve can passivate the perovskite quantum dots and reduce the defect density of the perovskite quantum dots. At the same time, the potassium salt can also be used as a sealing agent for the molecular sieve during the high-temperature solid phase reaction, further improving the water and oxygen resistance and fluorescence stability of the perovskite quantum dots. The small-sized molecular sieve also maximizes the effect of super-resolution imaging.
[0005] The purpose of the present invention can be achieved by the following technical solution: A small-sized stable water-soluble perovskite quantum dot composite material comprises an all-inorganic perovskite quantum dot and a small-sized molecular sieve encapsulating the perovskite quantum dot in a mass ratio of 1:2-3. Preferably, the mass ratio of the all-inorganic perovskite quantum dot to the small-sized molecular sieve is 1:3.
[0006] Furthermore, the small-size molecular sieve is prepared by the following method:
[0007] The template, hydrolyzing agent, potassium halide and solvent are mixed, heated and stirred at 40-80°C for 1-2 hours, the silicon source is added to the mixed solution at a flow rate of 4-6 ml / min, and the temperature is maintained at 40-80°C and the mixing and stirring are continued for 1-2 hours; the obtained white emulsion is centrifuged, washed, dried and calcined to obtain a small-sized molecular sieve.
[0008] Furthermore, the molar ratio of the silicon source, template, hydrolyzing agent, potassium halide and solvent is 1:0.06:0.07:0.03:80.
[0009] Further, the silicon source is tetraethyl orthosilicate or methyl orthosilicate, preferably tetraethyl orthosilicate;
[0010] The template agent is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium bromide, preferably hexadecyltrimethylammonium bromide;
[0011] The hydrolyzing agent is sodium hydroxide, ammonia or triethanolamine, preferably triethanolamine;
[0012] The potassium halide is potassium fluoride, potassium chloride, potassium bromide or potassium iodide, preferably potassium fluoride;
[0013] The solvent is water or ethanol, preferably water.
[0014] Preferably, the temperature of the mixed reaction is 40-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc., preferably 55°C.
[0015] Preferably, the mixing reaction time is 1-3 h, for example, 1 h, 2 h, 3 h, etc., preferably 2 h.
[0016] Furthermore, the white emulsion is dried to obtain a white powder, which is calcined in a tubular furnace under a nitrogen atmosphere for 0.5 to 2 hours, and in a muffle furnace under an air atmosphere for 3 to 6 hours, and calcined at 5-25°C / min to 500 to 600°C to obtain a pure white powdery small-size molecular sieve having a particle size of 35-50nm.
[0017] Preferably, the calcination temperature is 550°C.
[0018] Preferably, the heating rate of calcination is 5-25°C / min, for example, 5°C / min, 10°C / min, 15°C / min, 20°C / min or 25°C / min, etc., preferably 10-15°C / min.
[0019] In the present invention, the concentration of the blended potassium salt in the reaction is 60 mM. If the potassium salt concentration is too high, the particle size of the prepared molecular sieve will be too large, which is not conducive to biological imaging applications; if the potassium salt concentration is too low, some quantum dots will not be well fixed by the molecular sieve, which will affect the photoinduced quantum yield of the perovskite to a certain extent.
[0020] The present invention also provides a method for preparing a small-sized stable water-soluble perovskite quantum dot composite material, comprising the following steps: adding an all-inorganic perovskite quantum dot precursor to deionized water, heating and mixing at 60-90°C (preferably 80°C) for 20-40 minutes (preferably 30 minutes), then adding a small-sized molecular sieve, continuing to stir and react for 10-30 minutes (preferably 20 minutes), and finally adding a halide salt and mixing and stirring for 1-3 hours (preferably 2 hours), vacuum drying the obtained solution to obtain a yellow powder, and calcining at 600-700°C in argon to obtain the perovskite quantum dot composite material.
[0021] Furthermore, the all-inorganic perovskite quantum dot precursor is a mixture of CsI and PbI2 in a molar ratio of 1:1.
[0022] Furthermore, the halide salt is potassium iodide, potassium carbonate, potassium bromide or potassium chloride, preferably potassium iodide.
[0023] Furthermore, the calcination time is 10 to 60 minutes, and the calcination heating rate is 5 to 25°C / min.
[0024] The calcination temperature is 600-700°C, for example, it can be 600°C, 620°C, 640°C, 660°C, 680°C or 700°C.
[0025] In the present invention, if the calcination temperature is too low, the molecular sieve will not collapse completely, resulting in the molecular sieve being unable to completely collapse and encapsulate to protect the perovskite quantum dots from water and oxygen erosion in the environment; if the calcination temperature is too high, the molecular sieve skeleton will break, resulting in defects in the composite material.
[0026] Preferably, the calcination time of the mixture in step 2 is 10-60 min, for example, it can be 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc., preferably 30 min.
[0027] Preferably, the calcination heating rate of the mixture in step 2 is 5-25°C / min, for example, 5°C / min, 10°C / min, 15°C / min, 20°C / min or 25°C / min, and preferably 10-15°C / min.
[0028] The present invention also provides an application of a small-sized stable water-soluble perovskite quantum dot composite material, and the perovskite quantum dot composite material is used for biological cell fluorescence microscopy imaging.
[0029] The present invention uses a pre-prepared potassium salt-doped molecular sieve, and then mixes the perovskite quantum dot precursor with the prepared molecular sieve and then calcines it at a high temperature. The molecular sieve collapses and the potassium salt acts as a sealing agent to protect the perovskite quantum dots, thereby improving the water resistance and oxygen stability of the quantum dots. At the same time, the purification method of the method is simple, the stability is good, the particle size is small and uniform, and it has good commercial application prospects in biological imaging.
[0030] Moreover, the perovskite quantum dot composite material can be prepared without using polluted solvents during the preparation process, which is green and environmentally friendly.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention provides an all-silicon molecular sieve of about 40 nm (i.e., a self-made small-sized molecular sieve encapsulating perovskite quantum dots), wherein the molecular sieve is prepared by the method described above, which has no significant waste liquid discharge and is environmentally friendly. In addition, the molecular sieve has a small particle size and a mesoporous structure, and is an excellent mesoporous material candidate for drug delivery and encapsulation materials.
[0033] (2) The present invention provides a perovskite quantum dot composite nanomaterial of about 40 nm, which includes the all-silicon molecular sieve described above. The perovskite quantum dot is prepared by the method described above. The perovskite quantum dot material has a small particle size, good stability, and good anti-photobleaching performance, and can well meet the needs of fluorescent probes required for biological imaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of the preparation process of the composite molecular sieve MSN in Example 1 of the present invention;
[0035] Figure 2 This is a schematic diagram of the process of preparing perovskite quantum dot composite nanomaterials in Example 1 of the present invention;
[0036] Figure 3 The fluorescence spectra of the perovskite quantum dot composite nanomaterials of Example 1 and Comparative Example 1;
[0037] Figure 4 It is an X-ray diffraction spectrum of the perovskite quantum dot composite nanomaterial in Example 1 of the present invention;
[0038] Figure 5 The transmission electron microscope and particle size distribution diagram of the perovskite quantum dot composite nanomaterial in Example 1 of the present invention;
[0039] Figure 6 This is a biological cell fluorescence imaging image of the perovskite quantum dot composite nanomaterial in Example 1 of the present invention. DETAILED DESCRIPTION
[0040] The present invention will be described in detail below with reference to the accompanying drawings and embodiments. It should be noted that, for those skilled in the art, several changes and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
[0041] In the embodiment of the present invention, room temperature refers to 25°C.
[0042] Example 1
[0043] The present embodiment provides a perovskite quantum dot composite material, which includes perovskite quantum dots (PQDs) and an ultra-small size all-silicon molecular sieve MSN doped with metal K ions coated on the surface of the quantum dots, denoted as CsPbI3@MSN.
[0044] The present invention also provides a method for preparing a small-size perovskite quantum dot composite material CsPbI3@MSN, the preparation method comprising the following steps:
[0045] (1) Figure 1As shown, 0.73g hexadecyltrimethylammonium bromide and 0.17g potassium fluoride were mixed into 50ml ionized water, and 0.3ml triethanolamine was added to obtain a solution with a pH of 7.4. After mixing and stirring for 30min, 7.6ml tetraethyl orthosilicate was added at a flow rate of 5ml / min to obtain a white transparent solution. Stirring was continued for 2h to obtain a white emulsion. The K metal-doped molecular sieve was washed and centrifuged alternately with distilled water and ethanol for 3 times, and purified molecular sieve powder was obtained after drying. The obtained powder was calcined at a high temperature of 550°C for 5h to obtain a pure white powder, which was recorded as -MSN;
[0046] Wherein, the molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, potassium fluoride, triethanolamine and water is 1:0.06:0.03:0.07:80.
[0047] (2) Figure 2 As shown, 0.1mmol CsI was dissolved in 10ml deionized water, and then 0.1mmol PbI2 was added and mixed with ultrasound for 10min, and stirring was continued for 30min, and 0.21g of the prepared molecular sieve MSN was added, and mixed with ultrasound for 10min again, and then stirred at a speed of 500r / min for 20min, and then 0.1mmol KI solution was added; the obtained solution was vacuum dried at 60℃ for 12h, and the yellow powder mixture was ground and placed in a tube furnace. Under an argon atmosphere, the temperature was increased to 500℃ at a heating rate of 10℃ / min and calcined at a constant temperature for 15min, and then the temperature was increased to 700℃ at a heating rate of 10℃ / min and calcined at a constant temperature for 25min to obtain a crude product of a perovskite quantum dot composite material;
[0048] The crude product of the perovskite quantum dot composite material was cooled at room temperature, centrifugally washed three times with polar solvent DMF (N, N-dimethylformamide) and deionized water, and then dried in a vacuum drying oven at 60° C. to obtain a perovskite quantum dot composite material, recorded as CsPbI3@MSN.
[0049] Comparative Example 1
[0050] The difference between this comparative example and Example 1 is that the molecular sieve in step (2) is a commercial MCM-41 molecular sieve with a particle size of 500 nm-1 μm, that is, the obtained perovskite quantum dot composite material is CsPbI3@MCM-41.
[0051] The rest of the preparation methods and parameters were the same as those in Example 1.
[0052] The supernatants in Example 1 and Comparative Example 1 were respectively placed in a quartz cuvette to detect the fluorescence spectrum at 460 nm. The fluorescence spectrum of the perovskite quantum dot composite nanomaterials in Example 1 and Comparative Example 1 is as follows: Figure 3As shown, the peak position of the emission peak in Example 1 is slightly red-shifted, and there is no obvious difference in fluorescence intensity, indicating that the homemade all-silicon molecular sieve does not reduce the performance of the perovskite nanocomposite material while reducing its size.
[0053] like Figure 4 The XRD diffraction pattern of CsPbI3-MSN is shown, in which the diffraction pattern of CsPbI3 (purple line, PDF#18-0376) crystals is used as a reference. The XRD spectrum of the calcined sample is dominated by the broad peak of molecular sieve MSN, ranging from 15° to 35°, which belongs to the amorphous SiO2 matrix; secondly, it is consistent with the formation of a small amount of CsPbI3 NCs. When the temperature is increased, the characteristic peak of α-CsPbI3 appears, confirming the formation of CsPbI3-MSN core-shell nanocomposite materials in the present invention.
[0054] like Figure 5 The TEM image of CsPbI3-MSN is shown. Under the transmission electron microscope, the particle size of the perovskite nanocomposite material is between 35-50nm. From this data, it can be seen that the particle size of the perovskite quantum dot nanocomposite material provided by the present invention is about 40nm. The small particle size advantage of the present invention can be well applied to biological cell imaging, so that the perovskite material can give full play to its good fluorescence stability and high fluorescence quantum efficiency.
[0055] Hela cells were co-incubated with CsPbI3-MSN nanocomposites at a concentration of 50 μg / mL and co-stained with a nuclear dye (Hoechest 33324), as shown in Figure 6 Shown is the confocal fluorescence imaging of CsPbI3-MSN. Figure 6 a is the confocal fluorescence imaging of the perovskite CsPbI3-MSN nanocomposite in cells using 460nm excitation. Figure 6 b is the confocal fluorescence imaging of traditional nuclear dyes. Figure 6 c The results show that the CsPbI3-MSN nanocomposite can be well combined with the cell nucleus dye to obtain a complete cell image, proving the application of the CsPbI3-MSN core-shell nanocomposite in biological imaging. The confocal image shows that the cell morphology is good, indicating that the CsPbI3-MSN nanocomposite has low biological toxicity, and the emission wavelength is 550-720nm, which can be well applied to biological cell fluorescence microscopy imaging.
[0056] In summary, the present invention provides a method for preparing a perovskite quantum dot composite nanomaterial of about 40 nm, and provides a successful application of the perovskite quantum dot composite nanomaterial in biological imaging. The perovskite quantum dot composite nanomaterial has uniform particle size, good fluorescence stability, high fluorescence quantum efficiency, and high biological safety.
[0057] The applicant declares that since the particle size perovskite nanomaterial is closely related to its components, concentration and operation steps, a person skilled in the art can easily make various modifications to these embodiments and comparative examples, and apply the general principles described herein to other embodiments. A person skilled in the art should understand that any improvement to the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the scope of protection and disclosure of the present invention.
Claims
1. A small-sized stable water-soluble perovskite quantum dot composite material, characterized in that: It includes all-inorganic perovskite quantum dots with a mass ratio of 1:2 to 3 and small-sized molecular sieves encapsulating the perovskite quantum dots.
2. A small-sized stable water-soluble perovskite quantum dot composite material according to claim 1, characterized in that: The small-size molecular sieve is prepared by the following method: The template, hydrolyzing agent, potassium halide and solvent are mixed, heated and stirred at 40-80°C for 1-2 hours, the silicon source is added to the mixed solution at a flow rate of 4-6 mL / min, and the temperature is maintained at 40-80°C and the mixing and stirring are continued for 1-2 hours; the obtained white emulsion is centrifuged, washed, dried and calcined to obtain a small-sized molecular sieve.
3. A small-sized stable water-soluble perovskite quantum dot composite material according to claim 2, characterized in that: The molar ratio of the silicon source, template, hydrolyzing agent, potassium halide and solvent is 1:0.06:0.07:0.03:
80.
4. The small-sized stable water-soluble perovskite quantum dot composite material according to claim 2, characterized in that: The silicon source is ethyl orthosilicate or methyl orthosilicate; The template agent is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium bromide; The hydrolysis agent is sodium hydroxide, ammonia or triethanolamine; The potassium halide is potassium fluoride, potassium chloride, potassium bromide or potassium iodide; The solvent is water or ethanol.
5. The small-sized stable water-soluble perovskite quantum dot composite material according to claim 2, characterized in that: The white emulsion is dried to obtain a white powder, which is calcined in a tubular furnace under nitrogen atmosphere for 0.5 to 2 hours, or in a muffle furnace under air atmosphere for 3 to 6 hours, and calcined at 5-25°C / min to 500 to 600°C to obtain a pure white powdery small-size molecular sieve with a particle size of 35-50nm.
6. A method for preparing a small-sized stable water-soluble perovskite quantum dot composite material as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following steps: adding an all-inorganic perovskite quantum dot precursor into deionized water, heating and mixing at 60-90°C for 20-40 minutes, then adding a small-size molecular sieve, continuing to stir and react for 10-30 minutes, and finally adding a halide salt and mixing for 1-3 hours, vacuum drying the obtained solution to obtain a yellow powder, and calcining at 600-700°C in argon to obtain a perovskite quantum dot composite material.
7. The method for preparing a small-sized stable water-soluble perovskite quantum dot composite material according to claim 6, characterized in that: The all-inorganic perovskite quantum dot precursor is a mixture of CsI and PbI2 in a molar ratio of 1:
1.
8. The method for preparing a small-sized stable water-soluble perovskite quantum dot composite material according to claim 6, characterized in that: The halide salt is potassium iodide, potassium carbonate, potassium bromide or potassium chloride.
9. The method for preparing a small-sized stable water-soluble perovskite quantum dot composite material according to claim 6, characterized in that: The calcination time is 10 to 60 minutes, and the calcination heating rate is 5 to 25°C / min.
10. An application of a small-sized stable water-soluble perovskite quantum dot composite material as claimed in any one of claims 1 to 5, characterized in that: The perovskite quantum dot composite material is used for biological cell fluorescence microscopy imaging.